(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
Primary school aged pupils possess spoken language, but in school they are familiarized whith the written version of it as well. Also we have to know the characteristics of the spoken language used by the pupils, we know what kind of differences the pupils confront with during the acquisi- tion of the standard language. Students with dialectal backgrounds confront problems especi- ally in the acquisition of the spelling skills, regarding the field of spelling after pronunciation. It is especially important to know the mother tongue versions of the pupils. We examine the mistakes of the elementary school pupils in the West Hungarin region which can be explained on the basis of the dialect. In the free written composition of pupils,who are speakers of the West-Hungarian dialect we analyze the quantity of spelling mistakes which can be explained by the background of their dialects. We also examine which features of the West-Hungarian dialect have more influence on the pupils spelling skills.